Effect of drying plantain (Musa spp.) suckers prior to in vitro culture on reduction of lethal browning - AGBIDINOUKOUN, ARNAUD (My University, 2017)
This work aimed to evaluate the effect of drying plantain suckers on explants size, survival rate and browning intensity of plantain apices during in vitro culture. Three sets of suckers were used in the experiment. The first set used as a control and was not dried. The second set was dried under shade for 7 days and the third set was dried under shade for 14 days. Then explants were isolated. Comparative study was undertaken based on the immersion of explants in cysteine solution before in vitro culture. According to their size, two kinds of explants were isolated from each set (0.5 cm × 0.5 cm and 1 cm × 1 cm). The explants of 0.5 cm × 0.5 cm were introduced directly in culture after isolation. The explants of 1 cm × 1 cm were divided into two sub-sets. The explants isolated from the first sub-set were briefly immersed in 50 mg/l cysteine solution before in vitro culture. The second sub-set was introduced directly in the culture. The results showed that when the suckers are dried under shade for both of 7 and 14 days it reduced tissue browning and increased number of apices survived than the brief immersion of explants in 50 mg/l solution of cysteine. The response of explants varied with their sizes (0.5cm × 0.5 cm vs 1cm × 1 cm). Thus, explants with the size of 1 cm × 1 cm isolated from suckers dried for 7 days was the best treatment as 100% survival rate of material was observed during the four weeks of culture. As a result first subculture can be carried out after 4 weeks of culture instead of one to two weeks as recommended under other conditions. This method consumes less time and material, easy to perform and reduces the risk of loss of material during subcultures.
Keywords: browning intensity; suckers drying; banana and plantain tissue culture; apices survival